Validation of the Objective Structured Assessment of Technical Skill in Brasil - Campos,Marcelo Esteves Chaves (2020)
SUMMARY BACKGROUND The aim of this study was to perform a cross-cultural adaptation of the Objective Structured Assessment of Technical Skill (OSATS) tool into Brazilian Portuguese and to determine its reproducibility and validity in Brasil. METHODS A Brazilian Portuguese version of OSATS was created through a process of translation, back-translation, expert panel evaluation, pilot testing, and then its validation. For the construct and the concurrent validities, twelve participants were divided into a group of six experts and six novices, who had to perform tasks on a simulation model using human placentas. Each participant was filmed, and two blinded raters would then evaluate their performance using the traditional subjective method and then the Brazilian Portuguese version of OSATS. RESULTS The Brazilian Portuguese version of OSATS had the face, content, construct, and concurrent validities achieved. The average experts’ score and standard deviations were 34 and 0.894, respectively, for Judge 1 and 34.33 and 0.816 for Judge 2. In the case of novices, it was 13.33 and 2.388 for Judge 1 and 13.33 and 3.204 for Judge 2. The concordance between the judges was evident, with the Correlation Coefficient (Pearson) of 0.9944 with CI 95% between 0.9797 and 0.9985, with p < 10-10, evidencing the excellent reproducibility of the instrument. CONCLUSION This preliminary study suggests that the Brazilian Portuguese version of OSATS can reliably and validly assess surgical skills in Brasil.